The discrimination conundrum in the appointment of arbitrators in international arbitration - Oseni, Umar Aimhanosi; Kadouf, Hunud Abia (Kluwer Law International, 2012)
The problem of discrimination in the appointment of arbitrators has recently drawn considerable amount of attention from both practitioners and researchers alike in the field of international arbitration. A number of problems endemic to international arbitrations, including that of racial biases, have already been addressed by researchers in the field. However, the issue of racial and religious discrimination is of special interest and requires serious debate.This article attempts to discuss the issue of racial and religious discrimination in light of the recent decision of the Supreme Court of the United Kingdom in Jivraj v. Hashwani [2011] UKSC 40.The article tries to suggest a balanced view for promoting sustainable practices in international arbitration. This article further tries to emphasize the point that while party autonomy should be respected in all cases, nevertheless, parties should not be encouraged to introduce discriminatory elements in their arbitration agreements.